Artificial inoculation with Stenocarpella maydis in hybrids of maize - Rizzardi, Diego Ary; Faria, Cacilda Marcia Duarte Rios; Faria, Marcos Ventura; Mendes, Marcelo Cruz; Rossi, Evandrei Santos; Figueiredo, Alex Sandro Torre; Possato Junior, Omar (Scientia Agraria Paranaensis, 2017)
The aim of this work was to evaluate the behavior of commercial corn hybrids, with or without artificial inoculation of Stenocarpella maydis fungus. Experiments were conducted along the harvesting periods of 2010/11 and 2011/12, in Guarapuava, Paraná State, Brazil. Treatments were evaluated in a factorial scheme 4 (commercial hybrids) x 2 (with and without artificial inoculation). The statistical design was a randomized full blocks in a factorial scheme. The following characteristics were evaluated, amount of rancid grains, weight of a thousand grains and yield of grains. There was an impact of agricultural harvest on the incidence of rancind grains independently of artificial inoculation with S. maydis fungus. Hybrid DKB390Y was prominent as the genotype most susceptible to S. maydis fungus independently of the agricultural harvest and the presence or not of artificial inoculation.